Assessment of indoor environmental quality in elderly care centers - Cano, M. (2017)
The aim of this study was to characterize indoor environmental quality in a representative sample of Elderly Care Centers (ECC) in order to associate it with ventilation, health and comfort of elderly people. Indoor air quality (IAQ) parameters and thermal comfort were measured twice, during winter and spring/summer seasons, from 18 Elderly Care Centers (ECC) located in Lisbon, with a total of 116 rooms evaluated.